PERENCANAAN GEDUNG FTIK UIN TULUNGAGUNG DENGAN INSTALASI PEMBANGKIT LISTRIK TENAGA SURYA - safina salsabila (Jurnal Vokasi Teknik Sipil, 2024)
The FTIK building (Faculty of Tarbiyah and Teacher Training) is one of the buildings at the Sayyid Ali Rahmatullah State Islamic University, Tulungagung. A building with 5 floors and consisting of 26 classrooms costs an average of IDR 14,646,758/month for electricity. This research aims to reduce electricity costs by replacing the lights in the classrooms using PLTS. The lights were chosen using PLTS because considering the long duration of the lights on in the FTIK building, namely 15 hours/day. Research at the FTIK UIN Tulungagung Building using Monocrystalline panels with an On-Grid system. This research is quantitative. The calculation planning for this PLTS electrical installation requires 27 200Ah batteries, 28 panels with a capacity of 300 wp, and 5 60A controllers. Planning to save electricity costs of IDR. 1,021,860/month with electrical power of 42,120 wh, payback period of 7 years.